Extracellular ATP Induces Cytoplasmic and Nuclear Ca2+ Transients via P2Y2 Receptor in Human Biliary Epithelial Cancer Cells (Mz-Cha-1) - Elsing, Christoph; Georgiev, Tihomir; Hübner, Christian A.; Boger, Regina; Stremmel, Wolfgang; Schlenker, Thorsten (Anticancer research, 2012)
Extracellular nucleotides such as adenosine triphosphate (ATP) play a role in biliary epithelial cell function. Since nucleotide receptors are potential targets for various diseases related to epithelial cell dysfunction and cancer, the purpose of this study was to investigate the expression and to functionally characterize the nucleotide receptor subtypes in biliary epithelial cancer cells (Mz-Cha-1). Extracellular ATP dose-dependently resulted in an intracellular Ca2+ increase (mean effective concentration (EC50) 40 μM). Uridine triphosphate (UTP) produced a similar Ca2+ response and cross-desensitation was observed. The rank order of tested agonists was ATP=UTP>> adenosine>ADP=AMP>α,β-methylene-ATP. This confirms the functional expression of purinoceptor P2Y2 and P2Y4 in biliary epithelial cancer cell membranes. mRNAs for P2Y1, P2Y2, P2Y4 and P2Y6 purinergic receptor subtypes were found, whereas western blot analysis suggested only the expression of P2Y2 receptors. Confocal imaging and nuclear staining was used to compartmentalize ATP-induced cytosolic and nuclear Ca2+-transients, indicating a role for secretory ATP in regulating nuclear function, by increasing nuclear Ca2+ concentrations. These data define the expression profile of P2Y receptors on human biliary epithelial cancer cells and indicate P2Y2 receptors as being potential targets in new treatment strategies for biliary cancer.
Gesehen am 11.07.2019